2019
DOI: 10.1590/s1678-9946201961036
|View full text |Cite
|
Sign up to set email alerts
|

Detection of virulence genes in Salmonella Heidelberg isolated from chicken carcasses

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 27 publications
(48 reference statements)
6
49
0
4
Order By: Relevance
“…Several studies have found high prevalence of Salmonella Heidelberg in Brazil (Borges et al, 2019;Neves et al, 2016;Webber et al, 2019), corroborating with this study, where S. Heidelberg accounted for 41% of isolated serotypes. The high prevalence of this serotype has a great zoonotic importance, since S. Heidelberg has been shown to be more invasive compared to Typhimurium and Enteritidis in a study about Salmonella surveillance data from FoodNet collected during 1996-2006 in the United States (Jones et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have found high prevalence of Salmonella Heidelberg in Brazil (Borges et al, 2019;Neves et al, 2016;Webber et al, 2019), corroborating with this study, where S. Heidelberg accounted for 41% of isolated serotypes. The high prevalence of this serotype has a great zoonotic importance, since S. Heidelberg has been shown to be more invasive compared to Typhimurium and Enteritidis in a study about Salmonella surveillance data from FoodNet collected during 1996-2006 in the United States (Jones et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…S. Heidelberg was one of the main serovars implicated in large multistate outbreaks in humans in the United States, reportedly associated with the consumption of contaminated poultry and poultry products [7]. In South America, an increased occurrence of S. Heidelberg in poultry slaughterhouses was reported by the Brazilian government control programs [23]. In line with this, the European Commission also reported the detection of S. Heidelberg in frozen chicken liver imported from Brazil [24].…”
Section: Discussionmentioning
confidence: 96%
“…S. Heidelberg has the differential ability to survive in the environment (Webber et al, 2019) which may favour its persistence in the farms and the integrated companies. Interestingly, according to the PulseNet Argentine database, the PFGE pattern ARJF6X01.0025 was also found in 44% of S. Heidelberg isolates from both humans, food and animal origin in Argentina (https://pulse netin terna tional.org/netwo rks/latin ameri ca/).…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, this serotype has also emerged in other countries such as Brazil (Etter et al, 2019;Pandini et al, 2015;Webber et al, 2019), the United States (Deblais et al, 2018) and Colombia (Donado-Godoy et al, 2015). To understand whether S.…”
Section: Introductionmentioning
confidence: 99%